NON-DISSOLVED SOLIDS REMOVAL DURING PALM KERNEL OIL ULTRAFILTRATION - Mubiar Purwasasmita; Petrus Benny Juwono; Aysha Mareta Karlina; Khoiruddin Khoiruddin; I Gede Wenten (Reaktor, 2013)
Performance of polypropylene hollow fiber ultrafiltration membrane during non-dissolved solids (NDS) removal from palm kernel oil is investigated. The filtration is operated at difference feed temperature and pressure to study the effect of both parameters on membrane performance. From the experimental results, it can be concluded that polypropylene hydrophobic hollow fiber membrane can be used for palm kernel oil NDS removal. Temperature and trans-membrane pressure have proportional effect to permeate flux. In contrast, they have inverse effect to rejection of NDS. During the experiment, permeate fluxes and rejections of NDS varied from 3.4 to 8.7 L/m2.h and from 51% to 94%, respectively. The best operating conditions suggested are feed temperature of 30°C and TMP of 1 bar which produce the highest NDS rejection. In addition, the permeate quality can meet the requirement of standard NDS content even at its lowest rejection level which shows the remarkable performance of membrane filtration.